A randomized phase I clinical trial comparing the pharmacokinetic, safety, and immunogenicity of potential biosimilar recombinant human HER2 monoclonal antibody for injection and trastuzumab in healthy Chinese adults. (2nd July 2020) - Wang, Jiaxue; Niu, Suping; Dong, Wenliang; Wei, Li; Ou, Lun; Zhang, Tan; Zhang, Liangbi; Nie, Xiaoyan; Wang, Qian; Shen, Tiantian; Wang, Qi; Xia, Lin; et al.
ABSTRACT: Objectives: Recombinant human HER2 monoclonal antibody for injection (AK-HER2) is a potential biosimilar of trastuzumab (Herceptin®). This phase Ⅰ study aimed to demonstrate the pharmacokinetic (PK) equivalence between AK-HER2 and trastuzumab in healthy volunteers. Besides, safety and immunogenicity were investigated. Research design and methods: This was a randomized, double-blind phase Ⅰ trial in 96 healthy adults who received a single intravenous infusion of AK-HER2 or trastuzumab at 6 mg/kg. The primary PK endpoints were area under the serum concentration curve (AUC) from time 0 to the last time point (AUC0-t ) and peak concentration in serum (Cmax ). The PK bioequivalence was confirmed using the standard equivalence margins of 80%-125%. Results: The PK profiles of AK-HER2 and trastuzumab displayed high similarity. The geometric mean ratios (90% confidence intervals) of primary PK endpoints were within 80%-125%. The C max  and AUC 0-t  of female subjects in the AK-HER2 group were greater than those of male subjects (P <0.05). No infusion-related reactions (IRRs) or anti-drug antibody-positivity was observed after dosing. Conclusions: AK-HER2 was demonstrated to have highly similar PK to trastuzumab in healthy Chinese adults. Both drugs showed comparable safety and immunogenicity using dexamethasone as premedication to prevent IRRs..